PENGUKURAN MULTIDIMENSI DALAM KONSEP KEMISKINAN ISLAM: ANALISIS MENURUT PERSPEKTIF AL-QURAN DAN HADITH : Multidimensional Poverty Practices In Islamic Poverty Concept: Analysis According To Al-Quran And Hadith Perspectives - Abdul Rahman, Muhamad Zulfadli; Mohamad, Mohammad Taqiuddin; Abdul Azzis, Muhammad Shamshinor; M. Azizan, Ahmad Salahuddin (Jurnal Syariah, 2025)
Poverty is a global issue that affects all segments of society regardless of race or religion. Theoretically, poverty refers to a state where individuals are unable to meet their basic minimum needs. The limitations of conventional financial-based measurement methods have led many institutions to adopt a multidimensional approach to assessing poverty. This study analyzes the concept of multidimensional poverty in Islam based on the Quran and Hadith. A qualitative approach, utilizing textual analysis and scholarly interpretations, was employed to gain a holistic understanding of this concept. The findings reveal that Islam adopts a multidimensional approach, encompassing material elements such as food, clothing, and shelter, alongside spiritual aspects like psychological and spiritual well-being. This study has significant implications for social development policies by emphasizing the inclusion of spiritual dimensions as part of poverty measurement. This approach offers a comprehensive alternative for policymakers to design more effective programs to address poverty within Muslim communities.